Integration of House of Risk and Analytic Network Process Methods in Mitigation of Risk in the Sugar Production Process - Riska Dewi, Nanda; Ernawati, Dira; Rahmawati, Nur (Journal La Multiapp, 2025)
PT.XYZ is a company engaged in manufacturing, specifically in the production of granulated sugar. The problem that occurs in this company is the increasing number of gravel sugar defects by 18% or 1,019.52 tons. This number far exceeds the defect limit set by the company of 5% or 283.2 tons per month. Therefore, the purpose of this study is to identify the risks of the sugar production process using the House of Risk (HOR) method and determine the best alternative for priority risk mitigation through the Analytic Network Process (ANP) method at PT.XYZ. The HOR method is used to identify and classify risks based on severity and likelihood. Furthermore, the ANP method is used to determine the priority of risk mitigation strategies by considering the interdependence between risks. The results of the study showed that through the Focus Group Discussion (FGD) approach, 25 risk events and 25 risk sources were obtained which will be used to determine the mitigation strategy in the House Of Risk (HOR) method. Based on the calculation results of the rate agreement for alternative (W) of 0.777778, it shows a fairly high level of conformity among respondents' answers in selecting risk mitigation alternatives. Based on the calculation results on the super decision software, the highest normalized value was obtained, namely in the Desuperheater alternative of 0.51145. With this research, it is expected to help companies in overcoming company problems and can increase profits for the company.